2017
DOI: 10.21767/2573-0320.100011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Transfusion Transmissible Infections in a Nigerian Tertiary Hospital

Abstract: Millions of lives are saved each year through blood transfusion. Nevertheless, blood unscreened for transfusion transmissible infections (TTI) is a major public health problem. The prevalence of HIV, HBsAg, HCV and syphilis among blood donors reflect the status in the community hence the need for this study. A total of 108 donors comprising 11 family replacement donors, 32 voluntary donors and 65 paid donors were tested for antibodies to HIV, HBsAg, HCV and, syphilis using rapid serological screening methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…This was slightly higher than the values from similar studies in the littoral region (13.7%) and North West 55555555555 region (10.5%) of Cameroon respectively [ 10 , 11 ]. It was also slightly higher than the values from studies in Ethiopia (12.4%) [ 19 ], Kenya (12%) [ 27 ], and Nigeria (13%) [ 28 ]. However, it was comparable to studies from Mozambique (18.7%) [ 29 ], and Ghana (18.3%) [ 30 ], but lower than the values in studies from Wolaita Sodo, Ethiopia (29.5%) [ 21 ], Equatorial Guinea (47.4%) [ 31 ], and Edea, Cameroon (21.2%) [ 32 ].…”
Section: Discussioncontrasting
confidence: 67%
“…This was slightly higher than the values from similar studies in the littoral region (13.7%) and North West 55555555555 region (10.5%) of Cameroon respectively [ 10 , 11 ]. It was also slightly higher than the values from studies in Ethiopia (12.4%) [ 19 ], Kenya (12%) [ 27 ], and Nigeria (13%) [ 28 ]. However, it was comparable to studies from Mozambique (18.7%) [ 29 ], and Ghana (18.3%) [ 30 ], but lower than the values in studies from Wolaita Sodo, Ethiopia (29.5%) [ 21 ], Equatorial Guinea (47.4%) [ 31 ], and Edea, Cameroon (21.2%) [ 32 ].…”
Section: Discussioncontrasting
confidence: 67%
“…The prevalence of HBV in this study is lower than the prevalence reported by other studies in most African countries. For instance, a study done in Nigeria, Mozambique and Equatorial Guinea had showed HBV (HBsAg) prevalence of 10.9%, 10.6%, 10.01% in their respective blood donors [ 17 , 26 , 31 ]. The socio-cultural difference, variances in population risks, high endemicity for HBV in most African countries might be the possible reasons for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…HCV prevalence in Gondar, Jigjiga and Hawasa were 0.8%, 0.7% & 0.6% respectively [ 11 , 29 , 32 ]. The prevalence of HCV in blood donors in Equatorial Guinea was 3.7% [ 31 ], in Kenya and Nigeria, it was 3.2% and 2.8% respectively [ 17 , 21 ]. As in other TTIs, the reason for the difference could be attributed to the prevalence of HCV in general population, difference in risk factors, and access to screening, care and support facilities.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the concern to know their serological status for free in a blood bank after having consented to risky sex before. Some studies carried out in some countries like Pakistan, Cameroon, the Netherlands, the Central African Republic (CAR) and Nigeria have also shown that new donors have high seropositivity [17,[19][20][21][22]. Sexual partner multiplicity was a risk factor that was statistically associated with HIV infection and significant (P = .001).…”
Section: Discussionmentioning
confidence: 92%